(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Government and society cannot promote and enforce ethical behavior solely through the utilization of ethical codes of conduct or through the promulgation of a plethora of legislation. Communities tend to equate moral values and moral norms with values and norms, which apply only to personal relations. Aristotle contended that humans are not inherently virtuous and that ethics must be taught and practiced. Public officials should take decisions solely in terms of the public interest. They should be as open as possible about all the decisions and actions that they take. They should give reasons for their decisions and restrict information only when the wider public interest demands it. So, the administrative openness and simplification may be considered as a paradigm shift for ethical governance in any country of this world. The freedom or right to information can be an instrument for making the administrative activities and processes open and simple for the citizens. This paper makes an effort to justify the title of the paper by highlighting structural dimension of information management system, medium of disseminating the information.